Ekstraksi albumin ikan gabus (Channa striata) pada titik isoeletriknya - Muhammad Asfar; Abu Bakar Tawali; Pirman Pirman; Meta Mahendradatta (Fakultas Pertanian Universitas Ichsan Gorontalo, 2019)
The high content of albumin in snakehead fish and proof of efficacy in clinical trials against several diseases, as well as the expensive commercial albumin preparations, making a snakehead fish alternative as a cheap source of albumin. The purpose of this study was to optimize the extraction, purification of albumin from snakehead fish to obtain higher levels of albumin. For that need to be investigated to obtain the isoelectric point of albumin extract with the greatest yield. Treatment research is the use of solvents is 0.9% NaCL and dilute HCL and extraction is by heating and without heating. The parameters tested were the determination of the isoelectric point, moisture content, albumin, and yield. The results obtained showed that the isoelectric point of albumin is at pH 4.6 with 62.9% albumin, 7.8% moisture content and yield of 11.6%.